Electrode and method for manufacturing electrode
By inserting metal cations into the MXene electrode and performing dissociation treatment, a low-impedance two-dimensional film is formed, which solves the problem of high impedance of the MXene electrode and improves its conductivity and application efficiency.
Patent Information
- Application Number
- CN202380042279.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-03-28
- Publication Date
- 2025-01-03
AI Technical Summary
The existing MXene electrodes have high impedance problems in applications in electrical devices, especially the high surface impedance, which affects their conductive performance and application efficiency.
By preparing a two-dimensional MXene film containing metal cations, the specific steps include preparing the MmAXn precursor, etching and removing part of A atoms, cleaning and inserting metal cations, forming an intercalation treatment, and obtaining an intercalation cleaning treatment through an ex vivo treatment, and finally, A low impedance electrode film is formed.
Low impedance and surface impedance of electrodes are achieved, and the conductivity and electrode performance are improved, suitable for a variety of electrical and biological electrode applications.
Smart Images

Figure CN119256373A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode and a method for manufacturing the electrode. Background Art
[0002] In recent years, MXene has attracted much attention as a new material with electrical conductivity. MXene is a so-called two-dimensional material, and as described later, is a layered material having one or more layers. Generally, MXene has the form of particles (which may include powder, flakes, nanosheets, etc.) of the layered material.
[0003] Currently, various studies are being conducted on the application of MXene in various electrical devices. For example, Patent Documents 1 and 2 describe that MXene can be used as an electrode for measuring neural signals in the form of a film (Patent Document 1).
[0004] Prior art literature
[0005] Non-patent literature
[0006] Non-patent literature 1: Nicolette Driscoll, et al., “Two-Dimensional Ti3C2 MXenefor High Resolution Neural Interfaces,” ACS Nano, 2018, Vol. 12, Issue 10, pp. 10419-10429
[0007] Non-patent literature 2: Nicolette Driscoll, et al., “MXene-infused bioelectronicinterfaces for multiscale electrophysiology and stimulation,” Science Translational Medicine, 2021, Vol. 13, Issue 612, article abf8629 Summary of the invention
[0008] Problems to be solved by the invention
[0009] An object of the present invention is to provide an electrode having low impedance, and preferably an electrode having low surface impedance. Another object of the present invention is to provide a method for producing the electrode.
[0010] Means for solving problems
[0011] The electrode of the present invention comprises a film containing two-dimensional particles.
[0012] The two-dimensional particle has at least a metal cation and one or more layers.
[0013] The above layer comprises the following formula: M m X n The layer body shown and the modification or terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom) present on the surface of the layer body,
[0014] (Formula M m X n middle,
[0015] M is at least one metal of Groups 3, 4, 5, 6, and 7, and contains at least a Ti atom,
[0016] X is a carbon atom, a nitrogen atom or a combination thereof,
[0017] n is greater than or equal to 1 and less than or equal to 4,
[0018] m is greater than n and less than 5),
[0019] The above metal cations include Li cations,
[0020] The content of Li cations in the two-dimensional particles is 5.4 mol or more per 100 mol of Ti atoms.
[0021] In addition, the method for manufacturing an electrode of the present invention includes the step of forming a film using two-dimensional particles.
[0022] The two-dimensional particles at least include an intercalation treatment substance, and the intercalation treatment substance is manufactured by the following manufacturing method, which includes:
[0023] (a) Prepare the following formula: M m AX n The precursor steps shown,
[0024] (Formula M m AX n middle,
[0025] M is at least one metal of Groups 3, 4, 5, 6, and 7, and contains at least a Ti atom,
[0026] X is a carbon atom, a nitrogen atom or a combination thereof,
[0027] A is at least one element of Group 12, 13, 14, 15, or 16,
[0028] n is greater than or equal to 1 and less than or equal to 4,
[0029] m is greater than n and less than 5);
[0030] (b) removing at least a portion of the A atoms from the precursor using an etching solution, thereby obtaining an etched product;
[0031] (c) a step of cleaning the etched product to obtain an etched and cleaned product; and
[0032] (d) mixing the etching and cleaning product with a metal compound containing metal cations to obtain an intercalation product in which the metal cations are intercalated into the etching and cleaning product,
[0033] The above-mentioned metal cations include Li cations.
[0034] Effects of the Invention
[0035] According to the present invention, it is possible to provide an electrode having low impedance, preferably an electrode having low surface impedance. In addition, the present invention can also provide a method for producing the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a schematic cross-sectional view showing a MXene particle of a layered material in one embodiment of the present invention, Figure 1 (a) represents a single-layer MXene particle, Figure 1 (b) shows multi-layer (two-layer in the example) MXene particles.
[0037] Figure 2 This is a schematic cross-sectional view schematically showing a conductive film in one embodiment of the present invention. DETAILED DESCRIPTION
[0038] Hereinafter, an electrode and a method for producing the same in one embodiment of the present invention will be described.
[0039] The electrode of the present invention comprises a film containing two-dimensional particles.
[0040] The two-dimensional particle has at least a metal cation and one or more layers.
[0041] The layer comprises a layer body represented by the following formula: and a modification or terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom) present on the surface of the layer body,
[0042] (wherein, M is at least one metal of Groups 3, 4, 5, 6, and 7, including at least Ti atoms,
[0043] X is a carbon atom, a nitrogen atom or a combination thereof,
[0044] n is greater than or equal to 1 and less than or equal to 4,
[0045] m is greater than n and less than 5),
[0046] The above metal cations include Li cations,
[0047] The content of the Li cations is 5.4 mol or more per 100 mol of Ti atoms.
[0048] The electrode of the present invention can show low impedance by having the above-mentioned structure. Although it should not be interpreted as a specific theory in a restrictive manner, it can be considered that the two-dimensional particles contained in the above-mentioned film are layered materials, but contain a certain amount of Li cations, so it is easy to give and receive charges, and the electrical conductivity is high. Therefore, it can be considered that by making the electrode have such a film, the impedance is suppressed to be lower, and the surface impedance is suppressed to be lower.
[0049] The above two-dimensional particles can be understood as layered materials or layered compounds, also expressed as "M m X n T s ", s is an arbitrary number. In the past, x or z was sometimes used instead of s. Typically, n can be 1, 2, 3 or 4, but is not limited thereto.
[0050] In addition, in the present invention, the above-mentioned layer may be referred to as a MXene layer, and the above-mentioned two-dimensional particles may be referred to as MXene two-dimensional particles or MXene particles.
[0051] In the above formula of MXene, M is preferably at least one selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo and Mn and contains at least Ti, and more preferably at least one selected from Ti, V, Cr and Mo and contains at least Ti.
[0052] The ratio of Ti atoms in M is preferably 50 atomic % or more and 100 atomic % or less, more preferably 70 atomic % or more and 100 atomic % or less, and further preferably 90 atomic % or more and 100 atomic % or less.
[0053] It is known that MXene is represented by the above formula: m X n Expressed as follows.
[0054] Sc2C, Ti2C, Ti2N, Zr2C, Zr2N, Hf2C, Hf2N, V2C, V2N, Nb2C, Ta2C, Cr2C, Cr2N, Mo2C, Mo 1.3 C.Cr 1.3 C, (Ti, V) 2C, (Ti, Nb) 2C, W2C, W 1.3 C, Mo2N, Nb 1.3 C.Mo 1.3 Y 0.6C (In the above formula, "1.3" and "0.6" mean approximately 1.3 (= 4 / 3) and approximately 0.6 (= 2 / 3), respectively.),
[0055] Ti3C2, Ti3N2, Ti3(CN), Zr3C2, (Ti,V)3C2, (Ti2Nb)C2, (Ti2Ta)C2, (Ti2Mn)C2, Hf3C2, (Hf2V)C2, (Hf2Mn)C2, (V2Ti)C2, (Cr2Ti)C2, (Cr2V)C 2. (Cr2Nb)C2, (Cr2Ta)C2, (Mo2Sc)C2, (Mo2Ti)C2, (Mo2Zr)C2, (Mo2Hf)C2, (Mo2V)C2, (Mo2Nb)C2, (Mo2Ta)C2, (W2Ti)C2, (W2Zr)C2, (W2Hf)C2,
[0056] Ti4N3, V4C3, Nb4C3, Ta4C3, (Ti, Nb) 4C3, (Nb, Zr) 4C3, (Ti2Nb2) C3, (Ti2Ta2) C3, (V2Ti2) C3, (V2Nb2) C3, (V2Ta2) C3, (Nb2Ta2) C3, (Cr2Ti2) C3, (Cr2V 2) C3, (Cr2Nb2)C3, (Cr2Ta2)C3, (Mo2Ti2)C3, (Mo2Zr2)C3, (Mo2Hf2)C3, (Mo2V2)C3, (Mo2Nb2)C3, (Mo2Ta2)C3, (W2Ti2)C3, (W2Zr2)C3, (W2Hf2)C3, (Mo 2.7 V 1.3 ) C3 (In the above formula, "2.7" and "1.3" mean approximately 2.7 (= 8 / 3) and approximately 1.3 (= 4 / 3), respectively.)
[0057] Typically, in the above formula, M includes Ti, and X can be a carbon atom or a nitrogen atom. Preferably, M can be Ti, and X can be a carbon atom. For example, MAX phase is Ti3AlC2, and MXene is Ti3C2T s (In other words, M is Ti, X is C, n is 2, and m is 3).
[0058] It should be noted that in the present invention, MXene may contain a relatively small amount of A atoms from the MAX phase of the precursor, for example, 10% by mass or less relative to the original A atoms. The residual amount of A atoms may preferably be 8% by mass or less, more preferably 6% by mass or less. However, even if the residual amount of A atoms exceeds 10% by mass, there is sometimes no problem depending on the purpose and use conditions of the two-dimensional particles.
[0059] The above two-dimensional particles are composed of Figure 1 The MXene particles 10a (single-layer MXene particles) schematically illustrated in (a) are a collection of particles of one layer of MXene (hereinafter referred to as “MXene particles”). More specifically, the MXene particles 10a have m X n The layer body shown (M m X n The MXene layer 7a is a modified or terminal MXene layer 3a, 5a existing on the surface of the layer body 1a (more specifically, at least one of the two surfaces facing each other in each layer). Therefore, the MXene layer 7a is also represented as “MXene layer 7a”. m X n T s ", s is an arbitrary number.
[0060] The above two-dimensional particles may include one or more layers. As multiple-layer MXene particles (multi-layer MXene particles), such as Figure 1 As schematically shown in (b), two layers of MXene particles 10b can be exemplified, but the present invention is not limited to these examples. Figure 1 1b, 3b, 5b, 7b in (b) and the above Figure 1 1a, 3a, 5a, and 7a of (a) are the same. Two adjacent MXene layers (e.g., 7a and 7b) of the multilayer MXene particle do not have to be completely separated and may be partially in contact. The MXene particle 10a is a particle in which the multilayer MXene particles 10b are separated from each other and exist as a single layer, and there are unseparated multilayer MXene particles 10b remaining to form a mixture of the single-layer MXene particles 10a and the multilayer MXene particles 10b.
[0061] Without limiting the present embodiment, the thickness of each layer (corresponding to the above-mentioned MXene layers 7a and 7b) contained in the MXene particles can be, for example, 0.8 nm or more and 5 nm or less, in particular 0.8 nm or more and 3 nm or less (may vary mainly depending on the number of M atomic layers contained in each layer). For each stack of multilayer MXene particles that may be included, the interlayer distance (or gap size, in Figure 1 The thickness (represented by Δd in (b)) may be, for example, 0.8 nm to 10 nm, particularly 0.8 nm to 5 nm, more particularly about 1 nm, and the total number of layers may be 2 to 20,000.
[0062] In one embodiment, the ratio of (the average value of the major diameter of the two-dimensional surface of the two-dimensional particle) / (the average value of the thickness of the two-dimensional particle) is 1.2 or more, preferably 1.5 or more, and more preferably 2 or more. The average value of the major diameter of the two-dimensional surface of the two-dimensional particle and the average value of the thickness of the two-dimensional particle can be obtained by the method described below.
[0063] The two-dimensional particles of the present embodiment preferably include MXene particles with a large number of layers. The above-mentioned "large number of layers" refers to, for example, the number of stacking layers of MXene layers is more than 7 layers. In addition, the thickness of the stacking direction of the MXene particles with a large number of layers is preferably greater than 15nm, more preferably greater than 18nm and less than 50nm, and further preferably greater than 18nm and less than 30nm. In addition, in the above-mentioned MXene particles with a large number of layers, the ratio of (the average value of the long diameter of the two-dimensional surface of the two-dimensional particle) / (the average value of the thickness of the two-dimensional particle) is, for example, greater than 5 and less than 50, preferably greater than 10 and less than 30, and more preferably greater than 11 and less than 20. Thus, by including MXene particles with a large number of layers, a large amount of metal cations can be easily included.
[0064] Examples of the MXene particles having a large number of layers include two-dimensional particles obtained without undergoing a delamination treatment.
[0065] The two-dimensional particles of the present embodiment also preferably include multilayer MXene particles with a small number of layers. The above-mentioned "small number of layers" means, for example, that the number of stacking of MXene layers is 6 or less. In addition, the thickness of the multilayer MXene particles with a small number of layers in the stacking direction is preferably 15nm or less, and more preferably 10nm or less. In addition, in the multilayer MXene particles with a small number of layers, the ratio of (the average value of the long diameter of the two-dimensional surface of the two-dimensional particle) / (the average value of the thickness of the two-dimensional particle) is greater than 1.2, preferably greater than 1.5 and less than 10, and more preferably greater than 2 and less than 5. Hereinafter, the "MXene particles with a small number of layers" are sometimes referred to as "few-layer MXene particles". In addition, single-layer MXene particles and few-layer MXene particles are sometimes collectively referred to as "single-layer·few-layer MXene particles". As a result, the film-forming properties of the film containing the two-dimensional particles can become good.
[0066] Examples of the single-layer or few-layer MXene particles include two-dimensional particles obtained by delamination treatment.
[0067] In one embodiment, the two-dimensional particles of the present embodiment preferably include the above-mentioned MXene particles with a large number of layers and single-layer · few-layer MXene particles. The proportion of the MXene particles with a large number of layers in the two-dimensional particles of the present embodiment may be preferably 20% by volume or more and 100% by volume or less, more preferably 30% by volume or more and 100% by volume or less, and further preferably 60% by volume or more and 100% by volume or less. Thus, two-dimensional particles containing a large number of metal cations can be easily obtained.
[0068] In one embodiment, the two-dimensional particles of the present embodiment preferably include monolayer MXene particles and few-layer MXene particles, i.e., monolayer·few-layer MXene particles. The proportion of monolayer·few-layer MXene particles having a thickness of 15 nm or less in the two-dimensional particles of the present embodiment may preferably be 0% by volume or more and 70% by volume or less, more preferably 0% by volume or more and 60% by volume or less, and further preferably 0% by volume or more and 25% by volume or less. Thus, the film-forming property of the film containing the two-dimensional particles can be improved.
[0069] (average value of the major diameter of the two-dimensional surface of a two-dimensional particle)
[0070] The average value of the major diameter of the two-dimensional surface of the two-dimensional particle of the present embodiment is preferably 1 μm or more and 20 μm or less. Hereinafter, the average value of the major diameter of the two-dimensional surface may be referred to as “average flake size”.
[0071] The larger the average flake size is, the better the orientation of the two-dimensional particles in the material containing the two-dimensional particles becomes. The orientation of the two-dimensional particles can be evaluated, for example, by the electrical conductivity of the material containing the two-dimensional particles.
[0072] The average value of the major diameter of the two-dimensional surface is preferably 1.5 μm or more, and more preferably 2.5 μm or more. In the case of delamination of MXene by ultrasonic treatment of MXene, most of the MXene is reduced to a major diameter of about several hundred nm by ultrasonic treatment, so it can be considered that the orientation of the two-dimensional particles of the film formed by the monolayer MXene delaminated by ultrasonic treatment is low.
[0073] From the viewpoint of dispersibility in a dispersion medium, the average value of the major axis of the two-dimensional surface is, for example, 20 μm or less, preferably 15 μm or less, and more preferably 10 μm or less.
[0074] As shown in the examples described later, the major diameter of the two-dimensional surface refers to the major diameter when each MXene particle is approximated as an ellipse in an electron microscope photograph, and the average value of the major diameter of the two-dimensional surface refers to the number average of the major diameters of more than 80 particles. As an electron microscope, a scanning electron microscope (SEM) or a transmission electron microscope (TEM) photograph can be used.
[0075] The average value of the major diameter of the two-dimensional particles of this embodiment can be measured by dissolving a material including the two-dimensional particles in a solvent and dispersing the two-dimensional particles in the solvent. Alternatively, the average value can be measured based on an SEM image of the material.
[0076] (Average value of the thickness of two-dimensional particles)
[0077] The average value of the thickness of the two-dimensional particles of this embodiment is preferably 1 nm or more and 15 nm or less. The above thickness is preferably 10 nm or less, more preferably 7 nm or less, and further preferably 5 nm or less. On the other hand, considering the thickness of a single-layer MXene particle, the lower limit of the thickness of the two-dimensional particle can be 1 nm.
[0078] The average value of the thickness of the two-dimensional particles is obtained as a number average size (for example, a number average of at least 40 particles) based on an atomic force microscope (AFM) photograph or a transmission electron microscope (TEM) photograph.
[0079] The two-dimensional particles preferably contain voids. When the two-dimensional particles contain voids, it is easier to contain a large amount of metal cations, and it is easier to obtain an electrode with high conductivity and low impedance.
[0080] The above-mentioned metal cations include monovalent Li cations, and may further include other metal cations.
[0081] The metal of the metal cation is different from the atom M. In addition, the metal of the metal cation is different from the atom A contained in the precursor described later.
[0082] In one embodiment, the content of Li cations in the two-dimensional particles can be 5.4 mol or more, preferably 5.4 mol or more and 67 mol or less, more preferably 5.4 mol or more and 20 mol or less, and further preferably 5.4 mol or more and 9.7 mol or less, relative to 100 mol of Ti atoms. Thus, the conductivity of the film containing the two-dimensional particles is improved, and an electrode with low impedance can be easily obtained.
[0083] The content of Li atoms in the two-dimensional particles may be, for example, 0.1% by mass or more and 20% by mass or less, further 0.1% by mass or more and 10% by mass or less, particularly 0.2% by mass or more and 3% by mass or less, and particularly 0.2% by mass or more and 0.5% by mass or less. Thus, the conductivity of the film containing the two-dimensional particles can be further improved, and an electrode with low impedance can be more easily obtained.
[0084] The contents of Ti atoms, Li atoms, metal cations, and Li cations in the two-dimensional particles can be measured by, for example, inductively coupled plasma atomic emission spectrometry (ICP-AES) or the like.
[0085] The content of Li cations in the above-mentioned metal cations may be, for example, 1 mol % to 100 mol %, preferably 70 mol % to 100 mol %, more preferably 80 mol % to 100 mol %, further preferably 90 mol % to 100 mol %.
[0086] The metal cations are typically present on the layer, that is, they may be in contact with the layer or may be present on the layer via other elements.
[0087] In one embodiment, the two-dimensional particles preferably include a first component having a large number of layers and a Li cation content of 5.4 mol or more per 100 mol of Ti atoms. The two-dimensional particles including the first component can easily form a film containing a large amount of metal cations while maintaining film-forming properties.
[0088] The thickness of the two-dimensional particles of the first component may preferably exceed 15 nm, more preferably 18 nm or more and 50 nm or less, and further preferably 18 nm or more and 30 nm or less, and the number of layers may preferably exceed 5 and be 50 or less, preferably exceed 10 or more and be 30 or less, and further preferably be 11 or more and 20 or less. In addition, in the two-dimensional particles of the first component, the content of Li cations may preferably be 5.4 mol or more and 69 mol or less, more preferably 5.4 mol or more and 9.7 mol or less, and further preferably 6 mol or more and 9.7 mol or less relative to 100 mol of Ti atoms. In addition, the two-dimensional particles of the first component preferably contain voids.
[0089] The content of the first component contained in the two-dimensional particles is preferably 20% by volume or more and 100% by volume or less, more preferably 30% by volume or more and 100% by volume or less, and further preferably 60% by volume or more and 100% by volume or less. Thus, a film containing a large amount of metal cations can be easily formed while maintaining film-forming properties.
[0090] The first component can be typically produced in the form of an intercalation product described below, but is not limited to being produced by this production method.
[0091] In one embodiment, the two-dimensional particles preferably include a second component having a small number of layers and a Li cation content of more than 0 mol and less than 5.4 mol per 100 mol of Ti atoms. This can improve film formability of a film including the two-dimensional particles.
[0092] The thickness of the two-dimensional particles of the second component may be preferably 15 nm or less, more preferably 10 nm or less, and the number of layers may be preferably 1 or more and 6 or less. In addition, in the two-dimensional particles of the second component, the content of Li cations may be preferably 1 mol or more and less than 5.4 mol, and particularly may be 5.3 mol or less, relative to 100 mol of Ti atoms.
[0093] In the two-dimensional particles, the content of the second component relative to 100 parts by volume of the first component is preferably 0% by volume to 70% by volume, more preferably 0% by volume to 60% by volume, and even more preferably 0% by volume to 25% by volume.
[0094] The second component can be typically produced as a delaminated product described later, but is not limited to being produced by this production method.
[0095] In the electrode of the present invention, the content of the two-dimensional particles contained in the film is preferably 70% by volume or more and 100% by volume or less, more preferably 80% by volume or more and 100% by volume or less, and further preferably 90% by volume or more and 100% by volume or less. Thus, an electrode with high conductivity and low impedance can be easily obtained.
[0096] Hereinafter, a method for producing two-dimensional particles will be described in detail, but the present invention is not limited to this embodiment.
[0097] The method for manufacturing the two-dimensional particles comprises:
[0098] (a) Prepare the following formula: M m AX n The precursor steps shown
[0099] (Formula M m AX n middle,
[0100] M is at least one metal of Groups 3, 4, 5, 6, and 7, and contains at least Ti,
[0101] X is a carbon atom, a nitrogen atom or a combination thereof,
[0102] A is at least one element of Group 12, 13, 14, 15, or 16,
[0103] n is greater than or equal to 1 and less than or equal to 4,
[0104] m is greater than n and less than 5); and
[0105] (b) removing at least a portion of the A atoms from the precursor using an etching solution to obtain an etched product,
[0106] It may further include:
[0107] (c) a step of cleaning the etched product to obtain an etched and cleaned product;
[0108] (d) mixing the etching and cleaning product with a metal compound containing metal cations to obtain an intercalation product in which the metal cations are inserted into the etching and cleaning product;
[0109] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is layered;
[0110] (f) washing the delamination treated product to obtain a delamination treated and washed product. The metal cation in the step (d) includes a Li cation.
[0111] In the present invention, etching processed products, etching cleaned products, intercalation processed products, delamination processed products, and delamination cleaned products may all be included in the technical scope of two-dimensional particles.
[0112] Hereinafter, each step will be described in detail.
[0113] Process (a)
[0114] First, a predetermined precursor is prepared. The predetermined precursor that can be used in this embodiment is a MAX phase that is a precursor of MXene.
[0115] By the following formula: M m AX n express
[0116] (Formula M m AX n middle,
[0117] M is at least one metal of Groups 3, 4, 5, 6, and 7, and contains at least Ti,
[0118] X is a carbon atom, a nitrogen atom or a combination thereof,
[0119] A is at least one element of Group 12, 13, 14, 15, or 16,
[0120] n is greater than or equal to 1 and less than or equal to 4,
[0121] m is greater than n and less than 5).
[0122] The above-mentioned M, X, n and m are as described above.
[0123] A is at least one element of Groups 12, 13, 14, 15, and 16, usually an element of Group A, representatively Groups IIIA and IVA. More specifically, it may include at least one selected from Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, S and Cd, preferably Al.
[0124] The MAX phase has a layer composed of A atoms located in the M m X n The MAX phase typically has a repeating unit in which one layer of X atoms is arranged between each layer of n+1 layers of M atoms (these layers are also collectively referred to as "M m X n layer”), and configure the layer of A atoms (“A atomic layer”) as the next layer of the layer of the n+1th M atoms, but is not limited to this.
[0125] The MAX phase can be produced by a known method. For example, TiC powder, Ti powder and Al powder are mixed in a ball mill, and the obtained mixed powder is fired in an Ar atmosphere to obtain a fired body (massive MAX phase). Then, the obtained fired body is crushed with an end mill to obtain a powdered MAX phase for the next step.
[0126] Process (b)
[0127] In step (b), etching is performed using an etching solution to remove the precursor M m AX n The etching process is performed to remove at least a portion of the A atoms. m X n In the state of the layers shown, a processed product can be obtained in which at least a part of the layer composed of A atoms is removed.
[0128] The etching solution may contain an acid such as HF, HCl, HBr, HI, sulfuric acid, phosphoric acid, nitric acid, etc., and typically, an etching solution containing F atoms may be used. Examples of the etching solution include a mixture of LiF and hydrochloric acid; a mixture of hydrofluoric acid and hydrochloric acid; a mixture containing hydrofluoric acid, etc., and these mixtures may further contain phosphoric acid, etc. The etching solution may typically be an aqueous solution.
[0129] As the etching operation and other conditions using the above-mentioned etching solution, the conditions conventionally performed can be adopted.
[0130] Process (c)
[0131] In step (c), the product obtained by etching is cleaned to obtain an etching-cleaned product. By cleaning, the acid and the like used in the etching process can be sufficiently removed.
[0132] Cleaning can be carried out using a cleaning solution, and typically, can be carried out by mixing the etched product with the cleaning solution. The cleaning solution typically contains water, preferably pure water. On the other hand, in addition to pure water, it can further contain a small amount of hydrochloric acid, etc. The amount of cleaning solution mixed with the etched product and the mixing method of the etched product and the cleaning solution are not particularly limited. For example, as the mixing method, the etched product and the cleaning solution can be coexisted, stirred, centrifuged, etc. As the stirring method, stirring methods using hand shaking, automatic shaking, shear mixers, pot mills, etc. can be mentioned. The degree of stirring, such as the stirring speed and stirring time, can be adjusted according to the amount, concentration, etc. of the etched product to be processed. The above-mentioned cleaning with the cleaning solution can be carried out more than once, and it is preferred to carry out the cleaning using the cleaning solution multiple times. For example, specifically, the above-mentioned washing with a washing liquid can be carried out by sequentially carrying out step (i) (adding the washing liquid to the treated product or the remaining precipitate obtained in the following (iii)) and stirring, step (ii) centrifuging the stirred product, and step (iii) discarding the supernatant after centrifugation. For example, steps (i) to (iii) can be repeated in the range of 2 or more times, for example, 15 times or less.
[0133] Process (d)
[0134] In step (d), a metal compound containing a metal cation is used to perform an intercalation treatment on the etching and cleaning product to insert the metal cation, thereby obtaining an intercalation product. m X n The intercalation treatment between the layers can be carried out in a dispersion medium.
[0135] The metal cations may be the same as the metal cations contained in the two-dimensional particles, including Li cations, or may include other metal cations.
[0136] The metal of the metal cation is different from the M atom. In addition, the metal of the metal cation is different from the A atom contained in the precursor.
[0137] As the above-mentioned metal compound, there can be mentioned an ionic compound formed by bonding the above-mentioned metal cation and an anion. For example, there can be mentioned iodides, phosphates, sulfide salts including sulfates, nitrates, acetates, and carboxylates of the above-mentioned metal cations. As the above-mentioned metal cation, lithium ions are preferred, and as the metal compound, metal compounds containing lithium ions are preferred, more preferably ionic compounds of lithium ions, and further preferably one or more of iodides, phosphates, and sulfide salts of lithium ions. It can be considered that if lithium ions are used as metal ions, water hydrated with lithium ions has the most negative dielectric constant, so it is easy to form a single layer.
[0138] The specific method of intercalation treatment is not particularly limited. For example, the etched and cleaned product and the metal compound can be mixed and stirred or left to stand. For example, stirring at room temperature can be cited. The above stirring method can include, for example, a method using a stirring rod such as a stirrer, a method using a stirring blade, a method using a mixer, and a method using a centrifugal device. The stirring time can be set according to the manufacturing scale of the single-layer / few-layer MXene particles, for example, it can be set between 12 and 24 hours.
[0139] The intercalation treatment can be carried out in the presence of a dispersion medium, such as water, organic media such as N-methylpyrrolidone, N-methylformamide, N,N-dimethylformamide, methanol, ethanol, dimethyl sulfoxide, ethylene glycol, acetic acid, etc.
[0140] The order of mixing the dispersion medium, the etching cleaning product and the metal compound is not particularly limited. In one embodiment, the dispersion medium and the etching cleaning product may be mixed before the metal compound is mixed. Typically, the etching solution after etching may be used as the dispersion medium.
[0141] The intercalation treatment can be typically performed on the etched and cleaned product, but in another embodiment, it can also be performed on the above-mentioned precursor simultaneously with the etching treatment. Specifically, the etching and intercalation treatment includes the following steps: mixing a precursor, an etching solution, and a metal compound containing a metal cation, removing at least a portion of the A atoms from the above-mentioned precursor, and inserting the metal cation into the precursor from which the A atoms have been removed, thereby obtaining an intercalation product. In this way, it is possible to obtain a product in which at least a portion of the A atoms have been removed from the precursor (MAX), and the M in the precursor has been m X n Layer residue, in the adjacent multiple M m X n Intercalation treatment in which metal cations are inserted between the layers.
[0142] As the etching solution and the metal compound used in the etching and intercalation treatment, the same etching solution and the metal compound as used in step (b) can be used, respectively.
[0143] The intercalation treated material may be washed before being used in the manufacture of the electrode to obtain an intercalation washed material, which is also included in the scope of the intercalation treated material. Excessive metal compounds can be removed by washing the intercalation treated material.
[0144] The cleaning of the intercalated material can be carried out using a cleaning solution, and typically, it can be carried out by mixing the intercalated material with the cleaning solution. As the cleaning solution, the same cleaning solution as that in step (c) can be used, and the mixing can be carried out by the same method as the mixing method in step (c). For example, specifically, water can be used as the cleaning solution. In addition, the above-mentioned cleaning with the cleaning solution can be carried out by sequentially carrying out step (i) (adding the cleaning solution to the treated material or the remaining precipitate obtained in the following (iii)) and stirring, step (ii) centrifuging the stirred material, and step (iii) discarding the supernatant after centrifugation. It can be mentioned that steps (i) to (iii) are repeated within a range of more than 2 times, for example, less than 15 times.
[0145] Process (e)
[0146] In step (e), the intercalation product is stirred to separate the intercalation product into layers, thereby obtaining a layered product. By stirring, shear stress is applied to the intercalation product, and two adjacent M m X n At least a portion of the layers can be peeled off, and the MXene particles can be reduced to a single layer or a few layers.
[0147] The conditions for the delamination treatment are not particularly limited and can be carried out by known methods. For example, as a method for applying shear stress to the intercalation treatment material, a method of dispersing the intercalation treatment material in a dispersion medium and stirring can be cited. As a stirring method, stirring using a mechanical oscillator, a vortex mixer, a homogenizer, ultrasonic treatment, hand shaking, an automatic shaker, etc. can be cited. The degree of stirring such as the stirring speed and stirring time can be adjusted according to the amount and concentration of the treatment object to be treated. For example, after centrifuging the slurry after the above intercalation and discarding the supernatant, pure water is added to the remaining precipitate, for example, by hand shaking or stirring with an automatic shaker to perform layer separation. The removal of the unpeeled material can be cited as a process of washing the remaining precipitate with water after centrifugation and discarding the supernatant. For example, (i) adding pure water to the remaining precipitate after discarding the supernatant, (ii) centrifugation, and (iii) recovering the supernatant can be cited. The operations (i) to (ii) are repeated once or more, preferably twice or more and 10 times or less, to obtain a supernatant containing single-layer and few-layer MXene particles as a delamination product. Alternatively, the supernatant may be centrifuged, and the supernatant after centrifugation may be discarded to obtain clay containing single-layer and few-layer MXene particles as a delamination product.
[0148] Process (f)
[0149] In step (f), the delamination treated product is washed to obtain a delamination washed product. The washing can remove impurities and the like.
[0150] In one embodiment, the cleaning can be performed using a cleaning solution, and typically, the cleaning can be performed by mixing the delaminated product with the cleaning solution. In another embodiment, the cleaning can be performed by subjecting the delaminated product to an acid treatment and then mixing the acid-treated product with a cleaning solution. As the acid, inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, perchloric acid, hydroiodic acid, hydrobromic acid, and hydrofluoric acid can be used as appropriate; organic acids such as acetic acid, citric acid, oxalic acid, benzoic acid, and sorbic acid can be used as appropriate, and the concentration of the acid in the acid solution can be appropriately adjusted according to the delaminated product. In addition, the cleaning with the cleaning solution can be performed by sequentially performing step (i) (adding the cleaning solution to the treated product or the remaining precipitate obtained in (iii) below) and stirring, step (ii) centrifuging the stirred product, and step (iii) discarding the supernatant after centrifugation. It can be mentioned that steps (i) to (iii) are repeated within a range of 2 or more times, for example, 15 or less. The stirring can be performed using a hand shaker, an automatic shaker, a shear mixer, a pot mill, etc. The acid treatment may be performed once or more, and the mixing and stirring operation with a fresh acid solution (an acid solution not used in the acid treatment) may be performed twice or more, for example, 10 times or less, as required. As the cleaning liquid, the same cleaning liquid as that in step (c) may be used, and the mixing may be performed by the same method as that in step (c). Specifically, for example, water may be used as the cleaning liquid.
[0151] The intermediates and target products in the production methods described above, such as the intercalation products and delamination products, can be dried by suction filtration, heat drying, freeze drying, vacuum drying, or the like.
[0152] In one embodiment, the film may be binder-free. In another embodiment, the film may include, in addition to the two-dimensional particles, a resin. Examples of the resin include acrylic resins, polyester resins, polyamide resins, polyimide resins, polyamideimide resins, polyolefin resins, polycarbonate resins, polyurethane resins, polystyrene resins, polyether resins, polylactic acid, polyvinyl alcohol, and the like.
[0153] In addition, the above-mentioned film may further contain other additives.
[0154] In one embodiment, the electrode of the present invention can be formed only by the above-mentioned film. In another embodiment, the electrode of the present invention can include the above-mentioned film and one or more selected from a substrate and a protective layer. In addition, the above-mentioned electrode can be in a solid state or in a soft state with flexibility.
[0155] When the electrode of the present embodiment includes one or more selected from the group consisting of a substrate and a protective layer, the film may be in direct contact with the one or more selected from the group consisting of the substrate and the protective layer.
[0156] The substrate may be, for example, an inorganic material such as ceramics or glass, or an organic material. Examples of the organic material include flexible organic materials, specifically thermoplastic polyurethane elastomers (TPU), PET films, polyimide films, etc. In addition, the substrate may be a fiber material such as paper or cloth (for example, a sheet-like fiber material).
[0157] The protective layer may be a layer covering at least a portion or all of the film, and preferably may be a layer covering at least a portion of the film. The protective layer may be an organic material, specifically, may be a resin such as acrylic resin, polyester resin, polyamide resin, polyimide resin, polyamideimide resin, polyolefin resin, polycarbonate resin, polyurethane resin, polystyrene resin, polyether resin, polylactic acid, polyvinyl alcohol, etc.
[0158] In the electrode of this embodiment, the film may be exposed to the outside air so as to be in direct contact with the object to be measured, or may be covered with a substrate, a protective layer, or the like.
[0159] The method for manufacturing an electrode of the present invention includes the step of forming a film using the above-mentioned two-dimensional particles, wherein the two-dimensional particles at least include the above-mentioned intercalation treatment material, and may also include the intercalation treatment material, and the above-mentioned delamination treatment material and / or delamination cleaning treatment material. In one embodiment, the above-mentioned intercalation treatment material and delamination treatment material may be preferably included, and in another embodiment, the intercalation treatment material and delamination cleaning treatment material may be preferably included.
[0160] Although it should not be interpreted as a specific theory in a limiting sense, it can be considered that the above-mentioned intercalation treatment material contains metal cations, and the interlayer adhesion is moderately suppressed compared with the above-mentioned etching treatment material and etching cleaning treatment material. In addition, compared with the above-mentioned delamination treatment material and delamination cleaning treatment material, the above-mentioned intercalation treatment material contains a large amount of metal cations. Therefore, it can be considered that by using two-dimensional particles containing intercalation treatment materials, a film containing metal cations and having good film-forming properties can be obtained.
[0161] In addition, the two-dimensional particles used in the manufacturing method of the electrode of the present invention contain the above-mentioned intercalation treatment material, and it is believed that the intercalation treatment material can be peeled off to a certain extent due to shear stress during the film formation process. Therefore, film formation can be achieved even when the two-dimensional particles do not contain the above-mentioned delamination treatment material or delamination cleaning treatment material.
[0162] The formation of the above-mentioned film can be implemented, for example, by performing the following steps once or twice or more: vacuum filtering a mixed solution containing two-dimensional particles, a dispersion medium and the above-mentioned resin used as needed, or applying a mixed solution containing two-dimensional particles, a dispersion medium and the above-mentioned resin used as needed, and drying the dispersion medium.
[0163] For example, the supernatant containing the two-dimensional particles obtained by the delamination treatment (delamination product) and the intercalation product may be mixed and used as the mixed solution.
[0164] The mixed solution may be applied by spraying, for example, airless spraying or air spraying, and specifically, by spraying using a single-fluid nozzle, a two-fluid nozzle, a spray gun or the like.
[0165] As the above-mentioned dispersion medium, the same medium as the above-mentioned dispersion medium can be used, and examples thereof include water; organic medium such as N-methylpyrrolidone, N-methylformamide, N,N-dimethylformamide, methanol, ethanol, dimethyl sulfoxide, ethylene glycol, acetic acid, etc.
[0166] The proportion of the intercalation treatment material in the two-dimensional particles is preferably 20% by volume or more and 100% by volume or less, more preferably 30% by volume or more and 100% by volume or less, and further preferably 60% by volume or more and 100% by volume or less, in 100% by volume of the two-dimensional particles. Thus, a film containing a large amount of metal cations while maintaining film-forming properties can be easily formed.
[0167] In addition, regarding the total ratio of the intercalation treatment product, the delamination treatment product and the delamination cleaning treatment product in the above-mentioned two-dimensional particles, it is preferably greater than 0 volume % and less than 70 volume % in 100 volume % of the two-dimensional particles, more preferably greater than 0 volume % and less than 60 volume %, and further preferably greater than 0 volume % and less than 25 volume %.
[0168] The intercalation-treated product, the delamination-treated product, and the delamination-cleaned product can be produced by the above-mentioned production method, but are not limited thereto.
[0169] (Purpose of electrodes)
[0170] The electrode of the present embodiment can be used for any appropriate purpose. For example, the electrode used for electrochemical determination, the reference electrode, the electrode for electrochemical capacitor, the electrode for battery, the bioelectrode, the electrode for sensor, the electrode for antenna, the electrode for electrical stimulation, etc. can be cited. It can also be used for electromagnetic shielding (EMI shielding) and other purposes requiring high moisture resistance (for example, reducing the decrease of initial conductivity and preventing oxidation). The details of these uses are described below.
[0171] The electrode is not particularly limited, and may be, for example, a capacitor electrode, a battery electrode, a biosignal sensing electrode, a sensor electrode, an antenna electrode, an electrical stimulation electrode, etc. According to the electrode of the present invention, even with a smaller volume (device occupied volume), a large-capacity capacitor and battery, a low-impedance biosignal sensing electrode, a high-sensitivity sensor and antenna can be obtained.
[0172] The capacitor may be an electrochemical capacitor. An electrochemical capacitor is a capacitor that utilizes the capacity resulting from the physicochemical reaction between an electrode (electrode active material) and ions (electrolyte ions) in an electrolyte, and can be used as a device for storing electrical energy (electricity storage device). The battery may be a chemical battery that can be repeatedly charged and discharged. The battery may be, for example, a lithium ion battery, a magnesium ion battery, a lithium sulfur battery, a sodium ion battery, etc., but is not limited thereto.
[0173] The biological signal sensing electrode is an electrode for obtaining biological signals and may be, for example, an electrode for measuring EEG (electroencephalogram), ECG (electrocardiogram), EMG (electromyogram), or EIT (electrical impedance tomography), but is not limited thereto.
[0174] The sensor electrode is an electrode used to detect a target substance, state, abnormality, etc. The sensor may be, for example, a gas sensor, a biosensor (a chemical sensor using a molecular recognition mechanism of biological origin), etc., but is not limited to these.
[0175] The antenna electrode is an electrode used to radiate electromagnetic waves into space and / or receive electromagnetic waves in space. The antenna formed by the antenna electrode is not particularly limited as long as it is an antenna for mobile communications represented by mobile phones (so-called 3G, 4G, and 5G antennas), an antenna for RFID, or an antenna for NFC (Near Field Communication).
[0176] The electrical stimulation electrode is an electrode used to impart electrical stimulation to a living being. The electrical stimulation can be imparted to a living being, particularly to a biological tissue such as the spinal cord, brain, nerve tissue, muscle tissue, etc., but is not limited to these.
[0177] The electrode of the present embodiment can be used as a bio-signal sensing electrode. Since the electrode of the present invention has a low impedance, it is expected to contribute to sensing with higher spatial resolution and can be advantageously used to measure bio-signals such as EEG (electroencephalogram), ECG (electrocardiogram), EMG (electromyogram), and EIT (electrical impedance tomography).
[0178] The above describes in detail an electrode in one embodiment of the present invention and the two-dimensional particles used in the electrode, but various changes can be made. It should be noted that the electrode and the two-dimensional particles in the present invention can also be manufactured by a method different from the manufacturing method in the above embodiment. In addition, it should be noted that the manufacturing method of the electrode and the two-dimensional particles of the present invention is not limited to providing the electrode and the two-dimensional particles in the above embodiment.
[0179] The present invention includes the following contents.
[0180] [1]
[0181] An electrode comprising a film containing two-dimensional particles,
[0182] The two-dimensional particle has at least a metal cation and one or more layers.
[0183] The above layer comprises the following formula: M m X n The layer body shown and the modification or terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom) present on the surface of the layer body,
[0184] (Formula M m X n middle,
[0185] M is at least one metal of Groups 3, 4, 5, 6, and 7, and contains at least a Ti atom,
[0186] X is a carbon atom, a nitrogen atom or a combination thereof,
[0187] n is greater than or equal to 1 and less than or equal to 4,
[0188] m is greater than n and less than 5),
[0189] The above metal cations include Li cations,
[0190] The content of Li cations in the two-dimensional particles is 5.4 mol or more per 100 mol of Ti atoms.
[0191] [2]
[0192] The electrode according to [1], wherein the content of the Li cations in the two-dimensional particles is 5.4 mol or more and 9.7 mol or less per 100 mol of Ti atoms.
[0193] [3]
[0194] The electrode described in [1] or [2] is a biological signal sensing electrode.
[0195] [4]
[0196] A method for manufacturing an electrode, comprising the steps of forming a film using two-dimensional particles,
[0197] The two-dimensional particles at least include an intercalation treatment substance, and the intercalation treatment substance is manufactured by the following manufacturing method, which includes:
[0198] (a) Prepare the following formula: M m AX n The precursor steps shown
[0199] (Formula M m AX n middle,
[0200] M is at least one metal of Groups 3, 4, 5, 6, and 7, and contains at least a Ti atom,
[0201] X is a carbon atom, a nitrogen atom or a combination thereof,
[0202] A is at least one element of Group 12, 13, 14, 15, or 16,
[0203] n is greater than or equal to 1 and less than or equal to 4,
[0204] m is greater than n and less than 5);
[0205] (b) removing at least a portion of the A atoms from the precursor using an etching solution, thereby obtaining an etched product;
[0206] (c) a step of cleaning the etched product to obtain an etched and cleaned product; and
[0207] (d) mixing the etching and cleaning product with a metal compound containing metal cations to obtain an intercalation product in which the metal cations are intercalated into the etching and cleaning product,
[0208] The above-mentioned metal cations include Li cations.
[0209] [5]
[0210] According to the method for manufacturing an electrode described in [4], the two-dimensional particles further include a delaminated product, and the delaminated product is manufactured by the following manufacturing method, the manufacturing method comprising:
[0211] (e) A step of performing a delamination treatment of stirring the intercalation product to separate the intercalation product into layers, thereby obtaining a delaminated product.
[0212] [6]
[0213] According to the method for manufacturing an electrode described in [4] or [5], the two-dimensional particles further include a delamination-cleaned product, and the delamination-cleaned product is manufactured by the following manufacturing method, the manufacturing method comprising:
[0214] (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is layered;
[0215] (f) A step of washing the delamination treated product to obtain a delamination washed product.
[0216] [7]
[0217] The method for producing an electrode according to any one of [4] to [6], wherein the two-dimensional particle has at least the metal cation and one or more layers.
[0218] The above layer comprises the following formula: M m X n The layer body shown and the modification or terminal T (T is at least one selected from a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom) present on the surface of the layer body,
[0219] (Formula M m X n In the above, M, X, n and m have the same meanings as above),
[0220] The above metal cations include Li cations,
[0221] In the two-dimensional particle, the content of Li cations is 5.4 mol or more per 100 mol of Ti atoms.
[0222] Example
[0223] The present invention will be described in more detail below with reference to the following examples, but the present invention is not limited to these examples.
[0224] [Experimental Examples 1 to 6]
[0225] [Production of two-dimensional particles]
[0226] In Experimental Examples 1 to 6, (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning, (4) intercalation, and (5) delamination and cleaning were performed in sequence to produce intercalation products and delamination products.
[0227] (1) Preparation of precursor
[0228] TiC powder, Ti powder and Al powder (all made by Kojundo Chemical Laboratory Co., Ltd.) were put into a ball mill equipped with zirconia balls at a molar ratio of 2:1:1 and mixed for 24 hours. The obtained mixed powder was fired at 1,350°C for 2 hours in an Ar atmosphere. The obtained fired body (block) was crushed with an end mill to a maximum size of less than 40μm. Thus, Ti3AlC2 particles as a precursor (MAX) were obtained.
[0229] (2) Etching of precursor
[0230] The Ti 3 AlC 2 particles (powder) prepared by the above method were used to perform etching under the following etching conditions to obtain a solid-liquid mixture (slurry) containing a solid component (etched product) derived from the Ti 3 AlC 2 powder.
[0231] (Etching conditions)
[0232] Precursor: Ti3AlC2 (sieved with 45μm mesh)
[0233] Etching solution composition: 49% HF 6mL
[0234] H2O 18mL
[0235] HCl (12M) 36mL
[0236] Precursor input amount: 3.0g
[0237] Etching container: 100mL IBOY
[0238] Etching temperature: 35°C
[0239] Etching time: 24h
[0240] Stirrer speed: 400rpm
[0241] (3) Cleaning
[0242] The slurry was divided into two parts, each of which was inserted into two 50 mL centrifuge tubes. After centrifugation at 3500G for 5 minutes, the supernatant was discarded. 35 mL of pure water was added to each centrifuge tube, and the supernatant was separated and removed again at 3500G for 5 minutes. This operation was repeated 11 times. After the final centrifugation, the supernatant was discarded to obtain Ti3C2T s (The etching and cleaning product, hereinafter also referred to as "two-dimensional particles (c)") and clay as a water medium.
[0243] (4) Intercalation
[0244] For the above Ti3C2T s (Etching and cleaning treatment product) was treated with clay in a water medium, 0.75 g of LiCl and 37.2 g of pure water were added, and the mixture was stirred at 20° C. to 25° C. for 24 hours to perform intercalation using lithium ions as an intercalation agent, thereby obtaining an intercalation treatment product (hereinafter also referred to as "two-dimensional particle (d)"). The detailed conditions of the intercalation are as follows.
[0245] (Intercalation conditions)
[0246] Ti3C2T s - Moisture medium clay (etching and cleaning treatment): solid content 0.5g
[0247] Metal compound: 0.75 g LiCl
[0248] Intercalation container: 100mL IBOY
[0249] Temperature: 20°C or higher and 25°C or lower (room temperature)
[0250] Time: 24 hours
[0251] Stirrer speed: 700rpm
[0252] (5) Layering and cleaning
[0253] The slurry obtained by intercalation was put into a 50 mL centrifuge tube, and after centrifugation at 3,500G for 5 minutes using a centrifuge, the supernatant was recovered to obtain clay containing two-dimensional particles (delaminated product). Furthermore, after adding 35 mL of pure water, stirring with an oscillator for 15 minutes, centrifugation at 3,500G for 5 minutes was performed, and the supernatant was recovered as a liquid containing monolayer MXene particles. This operation was repeated 4 times to obtain a supernatant containing monolayer MXene particles. Furthermore, for the supernatant, centrifugation was performed at 4,300G for 2 hours using a centrifuge, and the supernatant was discarded to obtain clay containing delaminated washed products (hereinafter also referred to as "two-dimensional particles (f)").
[0254] 〔Preparation of slurry〕
[0255] The etching and cleaning products, intercalation products, and delamination and cleaning products were added to a 50 mL centrifuge tube in the proportions shown in Table 1, and pure water was added so that the proportion of two-dimensional particles combining the intercalation products and delamination and cleaning products was 1.5% by mass. Next, the mixture was stirred with an oscillator for 15 minutes to obtain a slurry.
[0256] 〔Electrode production〕
[0257] The slurry was added to a 25 mL syringe, and the syringe was placed on a spray coater. Next, a 3 cm square polyimide substrate was placed on a suction stage of the spray coater, and a film was formed by applying the slurry 15 times to obtain a laminate having a polyimide substrate and an undried film disposed on the polyimide substrate. The conditions during spraying were as follows.
[0258] (Spraying conditions)
[0259] Atomization pressure: 0.5MPa
[0260] Distance between nozzle tip and substrate: 15cm
[0261] ·Liquid delivery volume: 5mL / s
[0262] Scanning speed: 150mm / s
[0263] Stage heater: 45°C
[0264] The laminate was dried at 80° C. for 2 hours using a normal pressure oven, and then dried at 150° C. overnight under vacuum to form an electrode including a polyimide substrate and a film disposed on the polyimide substrate.
[0265] (Impedance measurement method)
[0266] The electrode was covered with Kapton (registered trademark) tape to have an opening of 10 mmφ, and used as a working electrode. A platinum electrode was used as a counter electrode, and a silver-silver chloride electrode was used as a reference electrode to assemble a beaker cell (Japanese: ビーカーセル). It should be noted that the counter electrode used had a larger area than the opening of the working electrode.
[0267] Next, the electrochemical measurement was performed in the potentiostat mode with the frequency set to 10 Hz, the voltage set to the open circuit voltage or 1 mVrms to 20 mVrms relative to the reference electrode, the number of plots set to 71 points, and the number of N per plot point set to 1 to 10. As the electrochemical measurement device, the VMP-300 high-performance electrochemical measurement system (16ch·Advanced model) from Bio-Logic Science Instruments was used.
[0268] (Measurement of Li atom content by inductively coupled plasma emission spectroscopy (ICP))
[0269] The electrode was dissolved by an alkali fusion method, and the obtained solution was measured by inductively coupled plasma atomic emission spectrometry (ICP-AES) to detect metal cations contained in the two-dimensional particles. iCAP6300 (manufactured by Thermo Fisher Scientific) was used for ICP-AES measurement.
[0270] The results are shown in Table 1. Experimental Examples corresponding to Comparative Examples of the present invention are indicated by a symbol "*", and other than that, they correspond to Examples of the present invention.
[0271]
Table 1
[0272]
[0273] Experimental Examples 1 to 3 are examples of the present invention, and electrodes with low impedance can be obtained. Experimental Examples 4 to 6 are examples in which the content of metal cations does not satisfy 5.4 mol per 100 mol of Ti atoms, and the impedance cannot be sufficiently satisfied.
[0274] Description of Reference Numerals
[0275] 1a, 1b: Layer body (Mm X n layer)
[0276] 3a, 5a, 3b, 5b: modified or terminal T
[0277] 7a, 7b: MXene layer
[0278] 10, 10a, 10b: MXene particles (two-dimensional particles of layered materials)
Claims
1. An electrode comprising a film containing two-dimensional particles, The two-dimensional particle has at least a metal cation and one or more layers, The layer comprises the formula: M m X n The layer body shown and the modification or terminal T present on the surface of the layer body, wherein T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom, Formula M m X n middle, M is at least one metal of Groups 3, 4, 5, 6, and 7, and contains at least a Ti atom, X is a carbon atom, a nitrogen atom or a combination thereof, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5, The metal cation comprises a Li cation, The content of Li cations in the two-dimensional particles is 5.4 mol or more per 100 mol of Ti atoms.
2. The electrode according to claim 1, wherein The content of the Li cations in the two-dimensional particles is 5.4 mol or more and 9.7 mol or less relative to 100 mol of Ti atoms. The electrode according to claim 1 or 2, which is a biological signal sensing electrode.
4. A method for manufacturing an electrode, comprising the step of forming a film using two-dimensional particles, The two-dimensional particles at least include an intercalation treatment substance, and the intercalation treatment substance is manufactured by the following manufacturing method, and the manufacturing method includes: (a) Prepare the following formula: M m AX n The precursor steps shown, Formula M m AX n middle, M is at least one metal of Groups 3, 4, 5, 6, and 7, and contains at least a Ti atom, X is a carbon atom, a nitrogen atom or a combination thereof, A is at least one element of Group 12, 13, 14, 15, or 16, n is greater than or equal to 1 and less than or equal to 4, m is greater than n and less than 5; (b) removing at least a portion of the A atoms from the precursor using an etching solution, thereby obtaining an etched product; (c) cleaning the etched product to obtain an etched and cleaned product; as well as (d) mixing the etching and cleaning product with a metal compound containing metal cations to obtain an intercalation product in which the metal cations are intercalated in the etching and cleaning product, The metal cations include Li cations.
5. The method for manufacturing an electrode according to claim 4, wherein: The two-dimensional particles further include a delamination-treated product, and the delamination-treated product is manufactured by the following manufacturing method, which includes: (e) A step of performing a delamination treatment of stirring the intercalated material to separate the intercalated material into layers, thereby obtaining a delaminated material.
6. The method for manufacturing an electrode according to claim 4 or 5, wherein: The two-dimensional particles further include a delamination-cleaned product, and the delamination-cleaned product is manufactured by the following manufacturing method, which includes: (e) stirring the intercalation product to obtain a delaminated product in which the intercalation product is layered; (f) A step of washing the delamination treated product to obtain a delamination washed product.
7. The method for producing an electrode according to any one of claims 4 to 6, wherein: The two-dimensional particle has at least the metal cation and one or more layers, The layer comprises the formula: M m X n The layer body shown and the modification or terminal T present on the surface of the layer body, wherein T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom and a hydrogen atom, Formula M m X n In the above, M, X, n and m have the same meanings as above. The metal cation comprises a Li cation, In the two-dimensional particle, the content of Li cations is 5.4 mol or more per 100 mol of Ti atoms.
